The Influence of Consumers Behavior on Wedang Uwuh Tea Bag Purchasing Decision - Shanindita, Kartika; Sadiyah, Fitria Naimatu; Puspitojati, Endah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Wedang Uwuh is a traditional drink typical of Yogyakarta made from various natural spices (ginger, second wood, nutmeg leaves, cinnamon leaves, clove handles, and other herbs). A large number of wedang uwuh industries in Yogyakarta cause fierce business competition.The study aimed to determine the influence of consumer behavior on the purchasing decisions of wedang uwuh Tea Bag, both partially and simultaneously. This research was a quantitative associative study with a descriptive approach. The sample selection used purposive sampling with Roscoe's theory, with a sample size of 50 respondents. Data were collected through interviews using a guided questionnaire. The influence of consumer behavior on purchasing decisions was analyzed using Multiple Linear Regression, Classical Assumption Tests, t-tests, F-tests, and Coefficient of Determination. The results showed that consumer behavior, including cultural, social, personal, and psychological factors, collectively influenced the purchasing decisions of brewed uwuh tea bags at CV Dewi Makmur. However, individually, cultural and personal factors had a significant influence on the purchasing decisions of brewed uwuh tea bags, while social factors and psychological factors did not have an impact on the purchasing decisions of wedang uwuh Tea Bag.